Concurrent occurrence of metastatic cutaneous melanoma and early feline diffuse iris melanoma in a cat - Eroksuz, Yesari; Babacan, Sumeyye; Polat, Eren; Issi, Mustafa; Timurkaan, Necati; Karabulut, Burak; Ekinci, Elif (Urmia Univ, 2025)
This report presented a case of the concurrent diagnosis of early feline diffuse iris melanoma (FDIM) and metastatic cutaneous melanoma in a tricolored mixed stray cat. Histopathological examination of biopsy samples identified melanoma on the nasal planum, lips along with metastasis to the submandibular lymph nodes. The initial treatment included surgical resection of the primary nasal planum neoplasm and the metastatic lesions in the submandibular lymph nodes. The necropsy, performed 40 days after the surgery, revealed the metastatic nodules in multiple organs including the liver, lungs, thyroids, pericardium, pleura, peritoneum, kidneys, and numerous lymph nodes. Histopathological examination revealed a biphasic neoplastic tissue composed of a mixture of epithelioid and spindle cells in primary and metastatic tumors. Additionally, the anterior surface of the iris contained 4-5 rows of melanocytic interstitial infiltration indicative of early FDIM. Immunohistochemical analysis revealed that the neoplastic cells showed positive immunoreactivity for Melan-A. To the authors' knowledge, this case represented the first reported case of concurrent FDIM and cutaneous melanoma in a feline patient.
Keywords: Cat; Cutaneous melanoma; Feline diffuse iris melanoma